TECHNICAL BARRIER TO TRADE OF INDONESIAN CLOVE CIGARETTES IN THE CONTEXT OF MEASURES AFFECTING THE PRODUCTION AND SALE OF CLOVE CIGARETTES UNITED STATES OF AMERICA (DS-406) - Adiwibowo, Yusuf (Jurnal IUS (Kajian Hukum dan Keadilan), 2013)
The members of WTO should obey the rules that have been agreed in the WTO. Every state has important role in international trade. The state should be able to protect its citizens from the negative effects of the trade itself. The role of state may be in providing the security and standardizing the trade of the so called a Technical Barrier to Trade and Sanitary and Pithosanitary. This study is aimed at determining the effect of âTechnical Barrier to Trade on Measures Affecting the Production and Sale of Clove Cigarettesâ on the Indonesian cigarettes This research employed a normative juridical. It is procedure of scientific research to find the truth based on a scientific legal logic in normative side. The research showedÂ  that the regulation onâTechnical Barrier to Tradeâ must be implemented fairly and non-discriminatory. The case between Indonesian clove cigarettes and the American menthol cigarette inshowed that the Law of âThe Family Smoking Prevention and Tobacco Control Actâ is not fairly implemented. . the United Stated of America should apply The Family Smoking Prevention and Tobacco Control Act. Keywords: Barrier, Regulation, Cigarettes, Menthol